Evaluasi Pengelolaan Obat Hipertensi Pada Tahap Pengadaan Dan Perencanaan di Gudang Farmasi Apotek Varia GATSU - Alex Handani Sinaga; Mandike Ginting (Jurnal Kesehatan Sejahtera, 2025)
Effective and efficient drug management is a crucial element in ensuring the availability of medications, especially for chronic diseases such as hypertension. This study aims to evaluate the management system of antihypertensive drugs during the planning and procurement stages at the pharmaceutical warehouse of Varia Pharmacy, located on Gatot Subroto Street (Gatsu). The main focus of this research is to identify the extent to which drug needs planning and procurement systems are appropriately implemented to support optimal pharmaceutical services. This study uses a descriptive qualitative method through direct observation, interviews with warehouse staff and pharmacists, as well as document reviews related to drug procurement and planning. The evaluation results indicate that the planning process for antihypertensive drugs is not entirely based on actual usage data but still relies on routine estimations that do not consider fluctuations in patient demand. Furthermore, there are challenges in procurement, such as delays in supplies from distributors and lack of synchronization between service units and the pharmaceutical warehouse. These issues have resulted in stockouts during certain periods, potentially disrupting the continuity of hypertension treatment. Therefore, it is recommended to implement a planning system based on historical data and to digitize the logistics process to improve efficiency. This research provides valuable insights for pharmacy managers to enhance drug management quality and patient service